The "Super-Utilizer" Inpatient: A Team-Based Care Plan for Frequent Admitters - Alrashidi, Afnan Abdullah; Alrashidi, Hanan Abdullah; Alrasheede, Gamyalh Saad; Alanazi, Saleh Binya; Alanze, Saud Mokhlif; Alharbi, Badar Kalifah; Aldajaani, Mohsen Dakhil Qablan; Alotaibi, Mohsen Dukhail; Basher, Hamza Eissa Abdullah; Al Dawseri, Mohammad Saeed Mordi; Aldosari, Ali Mordi Fahad; Aldawsari, Moubark Obaid Saad; et al. (Saudi Journal of Medicine and Public Health, 2024)
Background: A small subset of patients with complex medical, behavioral, and social needs—often termed "super-utilizers"—account for a disproportionately high volume of hospital admissions, readmissions, and healthcare expenditures. These individuals frequently cycle through acute care systems due to fragmented management of multimorbidity, polypharmacy, substance use, mental illness, and profound social determinants of health. Traditional, episodic hospital care fails to address the root causes of its utilization, leading to high costs, poor outcomes, and staff frustration. Aim: This narrative review synthesizes evidence from 2010-2024 on interdisciplinary, team-based inpatient care models specifically designed for super-utilizer patients. Methods: A comprehensive search of PubMed, CINAHL, Scopus, and health services research databases was conducted. Results: Evidence indicates that successful models hinge on early identification via health informatics flags, the co-creation of a unified care plan by residents and nurses, consistent relational care from health assistant nurses, and early physical therapy to combat deconditioning. These interventions, when bundled, demonstrate consistent reductions in 30-day readmission rates (15-40%) and length of stay for the target population by addressing clinical and psychosocial needs simultaneously. Conclusion: Managing super-utilizer inpatients requires a paradigm shift from reactive, disease-focused care to proactive, team-based stewardship of the whole patient. Investment in structured interdisciplinary protocols, supported by informatics and dedicated support roles, is essential to break the cycle of recurrent hospitalization and improve outcomes for this vulnerable population.